2019
DOI: 10.1021/acs.jmedchem.9b00359
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Recent Strategic Advances in Medicinal Chemistry

Abstract: Introducing novel strategies, concepts and technologies that speed up drug discovery and the drug development cycle is of great importance both in the highly competitive pharmaceutical industry as well as in academia. This review aims to present a "big-picture" overview of recent strategic innovations in medicinal chemistry and drug discovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 131 publications
(76 citation statements)
references
References 344 publications
(547 reference statements)
0
76
0
Order By: Relevance
“…Further investigation showed that the weak permeability and water solubility of these compounds were probably the important factors that are restricting their cell-based activity. Thus, in future research, we should pay attention to the evaluation of drug-like properties 36 while improving the activity of compounds. Generally, we analyzed the potential reasons for the anti-HIV-1 activity of compounds from various perspectives, which set the foundation for further design and optimization of CA-targeting compounds with improved potency.…”
Section: Resultsmentioning
confidence: 99%
“…Further investigation showed that the weak permeability and water solubility of these compounds were probably the important factors that are restricting their cell-based activity. Thus, in future research, we should pay attention to the evaluation of drug-like properties 36 while improving the activity of compounds. Generally, we analyzed the potential reasons for the anti-HIV-1 activity of compounds from various perspectives, which set the foundation for further design and optimization of CA-targeting compounds with improved potency.…”
Section: Resultsmentioning
confidence: 99%
“…A high-quality drug should emerge balanced e cacy against its therapeutic targets, safety, physicochemical properties and ADME properties. [26] In order to improve key drug-like properties, namely the solubility, an effort to identify prodrugs was undertaken. This has led to the discovery of a N-propionylsulfonamide prodrug HM-1.…”
Section: Discussionmentioning
confidence: 99%
“…Highlighted by Maria Emília de Sousa Photoactivatable molecules are considered in strategic advances in medicinal chemistry [51]. The concept of light liberating a photolabile protecting group has been used in photodynamic therapy or in prodrugs to control the activity of a bioactive compound in a more precise temporal release for specific effects.…”
Section: Visible Light Photoactivatable Prodrugs: Design Of the Platimentioning
confidence: 99%